Risk of flare in juvenile idiopathic arthritis: Is it related to the methotrexate treatment strategy or patient characteristics? - Rana İşgüder,; Zehra Kızıldağ,; Rüya Torun,; Tuncay Aydın,; Balahan Makay,; Erbil Ünsal, (Archives of Rheumatology, 2023)
Objectives: The study aimed to determine the factors that increase the risk of disease flare in patients with juvenile idiopathic arthritis who stopped methotrexate (MTX) monotherapy following inactive disease (ID). Patients and methods: In the retrospective study, files of all juvenile idiopathic arthritis cases between April 1992 and June 2022 were examined. Patients who stopped MTX monotherapy following ID were evaluated. Patients with disease flare and persistent ID were compared. Juvenile idiopathic arthritis subgroup, age of symptom onset, autoantibodies, acute phase reactants, MTX method of use, and withdrawal strategy were recorded. Systemic juvenile idiopathic arthritis patients were excluded from the study due to different clinical symptoms, diagnosis, and treatment methods. Results: Files of 1,036 patients were evaluated, and 107 patients (88 females, 19 males; mean age: 5.9±4.2 years; range, 0.8-16.5 years) were included in the study. The median age at symptom onset was 4.8 (interquartile range [IQR]: 2-7.6) years. In terms of juvenile idiopathic arthritis subgroups, 52 (48.6%) had oligoarticular juvenile idiopathic arthritis, 43 (40.2%) had polyarticular juvenile idiopathic arthritis, and 12 (11.2%) had juvenile psoriatic arthritis. The patients reached ID in nine (IQR: 4.8-17.7) months after starting MTX, and MTX treatment was discontinued after one (IQR: 0.7-1.3) year following ID. The disease flare developed in 59 (55%) of the cases. The ID continued in 48 (45%) patients. In multivariate analysis, the risk of flare was associated with younger symptom onset (odds ratio [OR]=2.2, p=0.006), antinuclear antibody positivity (OR=1.6, p=0.03), higher erythrocyte sedimentation rate (OR=1.01, p=0.04), and C-reactive protein (OR=1, p=0.02) at the MTX onset. No difference was observed between the two groups regarding MTX dose, route of administration, prior and concomitant treatments, time to reach ID, and time and method of MTX discontinuation. Conclusion: In this study, the risk of flare was associated with patient’s characteristics, rather than the administration and discontinuation method of MTX.